Correlation between Severity of Fetal Growth Restriction and Oxidative Stress in Severe Small-for-Gestational-Age Infants - Ashina, Mariko; Kido, Takumi; Kyono, Yuki; Yoshida, Asumi; Suga, Shutaro; Nakasone, Ruka; Abe, Shinya; Tanimura, Kenji; Nozu, Kandai; Fujioka, Kazumichi (International journal of environmental research and public health, 2021)
Severe small-for-gestational-age (sSGA) infants exhibit increased mortality and morbidity. Oxidative stress is suggested to be involved in intrauterine growth restriction. This retrospective study aimed to evaluate the oxidative stress level at birth in an sSGA population. Sera of 28 sSGA (sSGA group) and 31 non-sSGA (control group) infants, born at our hospital between March 2017 and March 2020, were evaluated. Oxidative stress (derivative of reactive oxidative metabolites: d-ROM level), biological antioxidant potential (BAP) level, and the ratio of d-ROM/BAP level (oxidative stress index: OSI) were measured. The sSGA group had a significantly lower birth weight (BW), BW z-score, head circumference, and height than the control group (all p < 0.05). No significant difference was noted in the BAP level; sSGA infants exhibited a significantly higher d-ROM level than control infants. sSGA infants showed a significantly increased OSI compared with control infants, and the BW z-score was inversely correlated with d-ROM levels and OSI in sSGA infants (R2 = 0.300; p < 0.01 and R2 = 0.319; p = 0.02, respectively) but not in controls. In conclusion, sSGA infants, including preterm infants, exhibited higher oxidative stress at birth. The severity of fetal growth restriction was significantly correlated with oxidative stress levels at birth in sSGA infants.